Integrating culturally sustaining pedagogies into elementary science instruction to foster inclusive character - Een Suhaeni; Faizatul Uyun; Ahmad Sahrudin (UHAMKA Press, 2026)
Abstract Purpose: This study investigates the systemic integration of Culturally Sustaining Pedagogies (CSP) into elementary science instruction to evaluate its impact on teacher pedagogical enactment fidelity and student inclusive character development. Design/methodology/approach: Employing a 14-week convergent parallel mixed-methods design, data were gathered from 12 primary teachers and 284 students (Grades 3–5) across four public elementary schools in Indonesia. Instruments included the validated Culturally Sustaining Science Enactment Rubric (CSSER). Findings: Quantitative analyses demonstrated statistically significant gains in teacher CSP enactment ( ) and student composite character traits ( ), occurring equitably across demographic subgroups. Qualitative findings revealed that legitimizing linguistic pluralism, community-connected inquiry, and critical socio-scientific consciousness served as pivotal mechanisms driving empathy, cultural humility, and collaborative agency. Practical implications: The findings provide primary educators, curriculum developers, and school leaders with an actionable instructional blueprint for embedding local socio-environmental phenomena and native language registers into science inquiry to nurture compassionate, equity-minded learners. Originality/value: This research bridges the divide between STEM conceptual learning and character education, establishing that CSP functions not merely as a tool for content acquisition, but as a direct driver of primary students' socio-ethical development.